Diversitas metodologi tafsir Al-Qur’an: Studi deskriptif-analitis atas tafsir bil Ma’tsur, bil Ra’yi, dan bil Isyari: - Fadhiel Al Faizi; Ulan Anggraini; M Afirstda Khairupitio; Riska Sawitri (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
This study examines three major approaches in Qur’anic interpretation: Tafsir bil Ma’tsur, Tafsir bil Ra’yi, and Tafsir bil Isyari. The issue addressed in this research is the diversity of interpretative methods used by Muslim scholars in understanding the Qur’an and how these approaches contribute to the development of Islamic scholarship. The purpose of this study is to describe the characteristics, sources, and methodological foundations of these three types of tafsir, as well as to analyze their roles in interpreting the meanings of the Qur’anic verses.This research employs a qualitative library research method. Data were collected through documentation and literature review from classical and contemporary Islamic scholarship, including books, journals, and authoritative works related to Qur’anic exegesis. The collected data were then analyzed using a descriptive-analytical approach to identify the differences and relationships among the three interpretative methods.The results of the research show that Tafsir bil Ma’tsur relies on transmitted sources such as the Qur’an, Hadith, and interpretations of the Companions and Tabi‘in. Tafsir bil Ra’yi emphasizes rational analysis and scholarly reasoning within the framework of Islamic principles, while Tafsir bil Isyari focuses on spiritual and inner meanings often associated with Sufi perspectives. In conclusion, these three approaches complement each other and enrich the understanding of the Qur’an from textual, rational, and spiritual dimensions